Preparation of monoalkylpiperidines via the mild hydrogenation of monoalkynylpyridines. Issue 29 (19th July 2017) - Usuki, Toyonobu; Komatsu, Akira
Graphical abstract: Highlights: Monoalkynylpyridines were prepared via Sonogashira cross-coupling reaction. Monoalkylpiperidines were prepared via mild hydrogenation of monoalkynylpyridines. The reactions proceeded in moderate to excellent yields. Abstract: Monoalkynylpyridines were prepared via a Sonogashira cross-coupling reaction between monoiodopyridines and alkynes. Mild hydrogenation of the obtained monoalkynylpyridines was then conducted to produce the corresponding monoalkylpiperidines in moderate to excellent yields. The hydrogenation reaction was carried out under H2 (1 atm) in the presence of 10 wt% Pd/C (5 eq) in either AcOH or MeOH at room temperature. The present mild method is therefore useful for the quick and easy preparation of monoalkylpiperidines.